Phenology, bunch morphology and must quality of five grapevine hybrids grafted onto two rootstocks - Souza, Juliana Rocha; Modesto, Lenon Romano; Juliano, Pedro Henrique Gatto [UNESP]; Hernandes, José Luiz; Tavares, Armando Reis; Tecchio, Marco Antônio [UNESP]; Moura, Mara Fernandes (FapUNIFESP (SciELO), 2021)
Phenology, bunch morphology, and must quality are essential factors to the selection of grapevine cultivars for winemaking. This study aimed to evaluate five grapevine hybrids grafted onto two rootstocks, looking for fruit with the best characteristics for producing wine. The hybrids studied were ‘BRS Lorena’, ‘IAC 21-14 Madalena’, ‘Moscatel de Jundiaí’, ‘Moscato Embrapa’ and ‘SR 0.501-17’ grafted onto ‘IAC 572 Jales’ and ‘IAC 766 Campinas’ rootstock. Phenology was evaluated weekly, and the number of days from pruning to sprouting, flowering, and maturation was calculated. Fruit production, bunch morphology, and must quality were evaluated for each genotype and rootstock. ‘SR 0.501-17’ was classified as a genotype with a medium cycle, with fruit maturing 20 days earlier than the other hybrids, which were, therefore, classified as late-cycling. No interaction was noted between hybrids and rootstocks relative to bunch morphology. The must of ‘Moscato Embrapa’ grafted onto ‘IAC 766 Campinas’ rootstock had higher maturation index than that grafted onto ‘IAC 572 Jales’ rootstock. ‘BRS Lorena’ and ‘SR 0.501-17’ produced smaller berries, must with medium acidity, and higher soluble solid contents, as compared with other hybrids, resulting in the best bunch morphology and must quality for winemaking.
Keywords: Fruits; Interaction; Vitis; Wine